Ethnomedicines in the 21st century: challenges and opportunities in the contemporary world - Wanzala, Wycliffe; Minyoso, Sheila I. (Journal of Medicinal Herbs and Ethnomedicine, 2024)
The ethnomedicine industry inherently developed de novo in the evolutionary history of humanity to provide healthcare services. This industry has existed long before the currently preferred conventional medicine and by then was the only trusted means of healthcare to humanity. Ethnomedicine has evolved and diversified into specializations along ethnic groupings worldwide. Nevertheless, attitude towards ethnomedicine is usually polarized varying from contemptuous dismissal to romantic glorification. Rarely does one come across people with balanced views. The discussion is based on 9 issues: view of ethnoknowledge of health from the early days, discovery and development of ethnomedicines, specializations in ethnomedicines, challenges and limitations, terminologies that shape ethnomedicine industry, merits and demerits of ethnomedicines, existing opportunities and the way forward. The ethnomedicine industry, just like any other field of professionalism, was not without challenges and limitations that affected its realization of full potential. In this discussion, 24 challenges and limitations are outlined but not limited to:- lack of information on standards, safety and efficacy, capacity building of ethnopractitioners, colonialism, climate change, witchcraft, socio-politics, recognition of ethnosystems, research and biased documentation, emerging diseases and pathogens, market value-chain, in-situ and ex-situ conservation, anthropogenic activities, sources of ethnomedicines, legal frameworks, harvesting, preparation, administration and storage methods, gender issues, poor remembrance of ethnomedical knowledge, existence of quackery, sources of ethnomedicines, biopiracy and bioprospecting, lack of mechanisms for monitoring and evaluation of ethnomedicines, advancement in human evolution and civilization, biological evolution and invasive alien species, stigmatisation due to poor perceptions and attitudes about ethnomedicines and competitive supremacy amongst ethnopractitioners and conventional practitioners, have all not favoured the industry. However, the use of ethnomedicines has tremendously increased and continues to increase albeit the above challenges and limitations facing the industry. The challenges and limitations are broadly and critically discussed while outlining opportunities and giving away forward.